A review of the mining adjustments to the In situ Rock Mass Rating - Pichuante, H.; Jakubec, J.; Thomas, A.; Elmo, D. (MassMin 2024: Proceedings of the 9th International Conference & Exhibition on Mass Mining, 2024)
One of the main challenges of caving projects is the realistic prediction of the undercut dimension at which caving will initiate and propagate. To address this need, empirical approaches were proposed, such as the cavability chart published by Diering & Laubscher (1987), which is based on the hydraulic radius and Modified Rock Mass Rating. Furthermore, the rock mass classification system used has limitations and is open to subjectivity, mainly due to its “mining adjustment factors” to convert In-situ Rock Mass Rating into Modified Rock Mass Rating. This study consists of a sensitivity analysis using a series of Finite-Discrete Element Models to evaluate the response of different conceptual rock masses characterized by the In-situ Rock Mass Rating system. These rock masses were assessed under different in-situ stress regimes and discontinuity arrangements to investigate the influence of these parameters on cave initiation and propagation. The results were compared with the most recent version of the Modified Rock Mass Rating system and its related cavability chart. This showed a poor match when comparing empirical predictions with the numerical model results under a low in-situ stress ratio, which means a higher adjustment must be applied for these cases, while a better agreement was observed for stress ratios between 1.5 to 2.5.